The Weibull functional form for SEP event spectra. (July 2015) - Laurenza, M; Consolini, G; Storini, M; Damiani, A
Abstract: The evolution of the kinetic energy spectra of two Solar Energetic Particle (SEP) events has been investigated through the Shannon's differential entropy during the different phases of the selected events, as proposed by [1]. Data from LET and HET instruments onboard the STEREO spacecraft were used to cover a wide energy range from ∼ 4 MeV to 100 MeV, as well as EPAM and ERNE data, on board the ACE and SOHO spacecraft, respectively, in the range 1.6 – 112 MeV. The spectral features were found to be consistent with the Weibull like shape, both during the main phase of the SEP events and over their whole duration. Comparison of results obtained for energetic particles accelerated at corotating interaction regions (CIRs) and transient-related interplanetary shocks are presented in the framework of shock acceleration.